Process heat transfer : principles, applications and rules of thumb. - Serth, R. W.; Lestina, Thomas G. (Academic Press, 2014)
A reference on the design and implementation of industrial heat exchangers. It provides the background needed to understand and master the commercial software packages used by professional engineers in the design and analysis of heat exchangers.